Reconciling Tourism Development and Conservation Outcomes Through Marine Spatial Planning for a Saudi Giga-Project in the Red Sea (The Red Sea Project, Vision 2030) - Chalastani, Vasiliki I.; Manetos, Panos; Al-Suwailem, Abdulaziz M.; Hale, Jason A.; Vijayan, Abhishekh P.; Pagano, John; Williamson, Ian; Henshaw, Scott D.; Albaseet, Raed; Butt, Faisal; Brainard, Russell E.; Coccossis, Harry; et al. (Frontiers in Marine Science, 2020)
.The Red Sea Project (TRSP) is a development that extends over 28,000 km2 along the shores of the Red Sea that will progress to become a sustainable luxury tourism destination on the west coast of the Kingdom of Saudi Arabia. The destination incorporates the Al Wajh lagoon, a pristine 2,081 km2 area that includes 92 islands with valuable habitats (coral reefs, seagrass and mangroves) and species of global conservation importance. The Red Sea Development Company, responsible for the execution of TRSP, has committed to achieve a net-positive impact on biodiversity while developing the site for sustainable tourism. This requires reaching conservation outcomes superior to those of a “business as usual” scenario for an undeveloped site. After careful optimization of the development plans to explore every opportunity to avoid impacts, we applied Marine Spatial Planning to optimize the conservation of the Al Wajh lagoon in the presence of development. We subsequently tested five conservation scenarios (excluding and including development) using Marxan, a suite of tools designed to identify priority areas for protection on the basis of prescribed conservation objectives. We succeeded in creating a three-layer conservation zoning achieving conservation outcomes as those possible in the “business as usual” scenario. Subsequently, we designed additional actions to remove existing pressures and generate net positive conservation outcomes. The results demonstrate that careful design and planning could potentially allow coastal development to enhance, rather than jeopardize, conservation.